A Large, Multicenter, Retrospective Study on Efficacy and Safety of Stereotactic Body Radiotherapy (SBRT) in Oligometastatic Ovarian Cancer (MITO RT1 Study): A Collaboration of MITO, AIRO GYN, and MaNGO Groups. (10th October 2019) - Macchia, Gabriella; Lazzari, Roberta; Colombo, Nicoletta; Laliscia, Concetta; Capelli, Giovanni; D'Agostino, Giuseppe Roberto; Deodato, Francesco; Maranzano, Ernesto; Ippolito, Edy; Ronchi, Sara; Paiar, Fabiola; Scorsetti, Marta; et al.
Abstract: Background: Recent studies have reported improvement of outcomes (progression‐free survival, overall survival, and prolongation of androgen deprivation treatment‐free survival) with stereotactic body radiotherapy (SBRT) in non‐small cell lung cancer and prostate cancer. The aim of this retrospective, multicenter study (MITO RT‐01) was to define activity and safety of SBRT in a very large, real‐world data set of patients with metastatic, persistent, and recurrent ovarian cancer (MPR‐OC). Materials and Methods: The endpoints of the study were the rate of complete response (CR) to SBRT and the 24‐month actuarial local control (LC) rate on "per‐lesion" basis. The secondary endpoints were acute and late toxicities and the 24‐month actuarial late toxicity‐free survival. Objective response rate (ORR) included CR and partial response (PR). Clinical benefit (CB) included ORR and stable disease (SD). Toxicity was evaluated by the Radiation Therapy Oncology Group (RTOG) and the European Organization for Research and Treatment of Cancer (EORTC) and Common Terminology Criteria for Adverse Events (CTCAE) scales, according to center policy. Logistic and Cox regression were used for the uni‐ and multivariate analysis of factors predicting clinical CR and actuarial outcomes. Results: CR, PR, and SD were observed in 291 (65.2%), 106 (23.8%), and 33 (7.4%) lesions, giving a rate of CB of 96.4%. Patient aged ≤60 years, planning target volume (PTV) ≤18 cm 3, lymph node disease, and biologically effective dose α/β10 > 70 Gy were associated with higher chance of CR in the multivariate analysis. With a median follow‐up of 22 months (range, 3–120), the 24‐month actuarial LC rate was 81.9%. Achievement of CR and total dose >25 Gy were associated with better LC rate in the multivariate analysis. Mild toxicity was experienced in 54 (20.7%) patients; of 63 side effects, 48 were grade 1, and 15 were grade 2. The 24‐month late toxicity‐free survival rate was 95.1%. Conclusions: This study confirms the activity and safety of SBRT in patients with MPR‐OC and identifies clinical and treatment parameters able to predict CR and LC rate. Implications for Practice: This study aimed to define activity and safety of stereotactic body radiotherapy (SBRT) in a very large, real life data set of patients with metastatic, persistent, recurrent ovarian cancer (MPR‐OC). Patient age <60 years, PTV <18 cm 3, lymph node disease, and biologically effective dose α/β10 >70 Gy were associated with higher chance of complete response (CR). Achievement of CR and total dose >25 Gy were associated with better local control (LC) rate. Mild toxicity was experienced in 20.7% of patients. In conclusion, this study confirms the activity and safety of SBRT in MPR‐OC patients and identifies clinical and treatment parameters able to predict CR and LC rate. Abstract : Traditional management of recurrent ovarian cancer is system chemotherapy. This article considers an alternative, focusing on the activity and safety of stereotactic body radiotherapy for patients with ovarian cancer.